Chapter Fifteen: Combating HIV & Aids among Persons with Disability: A Disability Perspective - Kabue, Samuel; Mombo, Esther (Disability, Society and Theology : Voices from Africa, 2012)
Disability, Society and Theology: Voices from Africa is the result of a workshop which brought together African theologians, persons with disabilities and disability expertise in the Region to prepare resource materials to enrich the disability study process in the context of the Africa region. The book is in six parts and includes contributions from scholars across the continent. The parts are: Disability Theology: Issue to Debate; The Able Disabled and the Disabled Church: The Churchís Response to Disability; Disability and Society; Disability Theology: Some Interfaces; Disability and Caregiving; and Disability in the African Experience.